Element of Consent in Statutory Rape Law: An Analysis Under the Malaysian Penal Code - Md Ismail, Che Thalbi; A. Rahman, Aspalella (Serials Publications, 2017)
Lack of consent is a necessary element in every rape case. However, making sexual contact with a minor or incapacitated person who actually consented does not mean that it is not a rape. This is because, the consent here may result from either forcible compulsion by the perpetrator or an incapacity to consent on the part of the victim. The law provides that persons who are physically or mentally helpless or who are under a certain age in relation to the perpetrator are deemed legally incapable of consenting to sex. This law automatically shows that the rapist is guilty of the offence of rape if the victim is under age even she consented to the act. Hence, this paper will discuss law relating to the rape offences involving under age under section 375(f) and (g) of the Malaysian Penal Code. A legal analysis will be made to see whether certain circumstances should be considered to release the accused on the basis of genuine consent given by a person. By giving this exception to certain genuine consent cases, the law is assumed to ensure the protection given to minors under section 375(g) is not misused